Cathepsin B-A Neuronal Death Mediator in Alzheimer’s Disease Leading to Neurodegeneration - Sharma A.; Swetha R.; Bajad N.G.; Ganeshpurkar A.; Singh R.; Kumar A.; Singh S.K. (My University, 2025)
The lysosomal cysteine protease enzyme, named Cathepsin B, mainly degrades the protein and manages its average turnover in our body. The Cathepsin B active form is mostly present inside the lysosomal part at a cellular level, providing the slightly acidic medium for its activation. Multiple findings on Cathepsin B reveal its involvement in neurons’ degeneration and a possible role as a neuronal death mediator in several neurodegenerative diseases. In this review article, we highlight the participation of Cathepsin B in the etiology/progress of AD, along with various other factors. The enzyme is involved in producing neurotoxic Aβ amyloid in the AD brain by acting as the β-secretase enzyme in the regulated secretory pathways responsible for APP processing. Aβ amyloid accumulation and amyloid plaque formation lead to neuronal degeneration, one of the prominent pathological hallmarks of AD. Cathepsin B is also involved in the production of PGlu-Aβ, which is a truncated and highly neurotoxic form of Aβ. Some of the findings also revealed that Cathepsin B specific gene deletion decreases the level of PGlu-Aβ inside the brain of experimental mice. Therefore, neurotoxicity might be considered a new pathological indication of AD due to the involvement of Cathepsin B. It also damages neurons present in the CNS region by producing inflammatory responses and generating mitochondrial ROS. However, Cathepsin B inhibitors, i.e., CA-074, can prevent neuronal death in AD patients. The other natural inhibitors are also equally effective against neuronal damage with higher selectivity. Its synthetic inhibitors are specific for their target; however, they lose their selectivity in the presence of quite a few reducing agents. Therefore, a humanized monoclonal antibody is used as a selective Cathepsin B inhibitor to overcome the problem experienced. The use of Cathepsin B for the treatment of AD and other neurodegenerative diseases could be considered a rational therapeutic target. © 2022 Bentham Science Publishers.